SEMINAR PARTISIPATIF PAK UNTUK MEMBENTUK KARAKTER REMAJA DI SMA NEGERI 3 AWAALAH, ALOR - Oematan, Tri Oktavia; Tandjung, Ferofianes Linda; Rohi, Januar Daniel Maxfrid; Sibulo, Deviana; Paat, Defrialdo; Matang, Nova Yufrida (Jurnal Abdi Insani, 2025)
Rapid social changes have posed significant challenges for Christian youth in Alor Regency, particularly in finding their identity, dealing with the influence of social media, and facing a decline in spiritual values. In this context, Christian Religious Education (CRE) plays an important role as a pillar of hope that strengthens faith and shapes the character of youth to live based on love, faith, and hope. This community service activity was conducted at SMA Negeri 3 Awalah, Alor, involving 65 tenth-grade students.This program aims to strengthen the faith identity of Christian youth, foster spiritual awareness, develop character grounded in love, faith, and hope, and equip them with relevant and contextual life strategies amid the dynamics of social change. The method used was an interactive seminar employing a reflective and participatory approach through presentations and discussions. This model encouraged active student participation, raised faith awareness, and reinforced Christian values in everyday life practices.The results showed a significant improvement in students’ understanding of Christian faith identity and the urgency of character formation rooted in love, faith, and hope. Through reflective processes and participatory discussions, students became more aware of the role of faith in addressing social and moral challenges in their environment. The activity was carried out effectively and successfully built a deeper understanding of the importance of Christian Religious Education as a pillar of hope in shaping the character of Christian youth with integrity and resilience in facing social change. More broadly, this program contributes to national development efforts through the formation of a young generation that is faithful, of strong character, and full of integrity in navigating the currents of social transformation.